Disparities in substance use disorder treatment use and perceived need by sexual identity and gender among adults in the United States. (1st September 2021) - Krasnova, Anna; Diaz, José E.; Philbin, Morgan M.; Mauro, Pia M.
Highlights: Past-year SUD treatment use was low among adults across sexual identity and gender. Most LGB adults perceived a greater SUD treatment need than heterosexuals. SUD treatment use odds were higher among bisexual women and gay men. Results support facilitating SUD treatment access and engagement among LGB adults. Abstract: Background: Substance use disorder (SUD) treatment use is low in the United States. We assessed differences in treatment use and perceived need by sexual identity (i.e., lesbian, gay, bisexual, heterosexual) and gender among adults with a past-year SUD. Methods: We pooled data from the 2015–2019 National Survey on Drug Use and Health for adults (18+) who met past-year DSM-IV SUD criteria and self-reported sexual identity (n = 21, 926). Weighted multivariable logistic regressions estimated odds of past-year: 1) any SUD treatment; 2) specialty SUD treatment; 3) perceived SUD treatment need by sexual identity, stratified by gender and adjusted for socio-demographics. Results: Any past-year SUD treatment use was low among adult men (heterosexual [10.4 %], gay [15.5 %], and bisexual [7.1 %]) and women (heterosexual [9.9 %], gay/lesbian [11.9 %], and bisexual [13.2 %]). Patterns were similar for specialty SUD treatment and perceived treatment need. Adjusted odds of any SUD treatment use were higher among gay men (aOR = 1.65 [95 % Confidence Interval 1.10−2.46]) and bisexual women (aOR = 1.31 [1.01−1.69]) than their heterosexual peers. Compared to their heterosexual counterparts, adjusted odds of perceived SUD treatment need were higher among bisexual women (aOR = 1.65 [1.22−2.25]), gay men (aOR = 1.76 [1.09−2.84]), and bisexual men (aOR = 2.39 [1.35−4.24]). Conclusions: Most adults with SUD did not receive treatment. Gay men and bisexual women were more likely to receive treatment and reported higher perceived SUD treatment need than heterosexual peers. Facilitating treatment access and engagement is needed to reduce unmet needs among marginalized people who perceive SUD treatment need.